The role of post-war reconstruction planning in Hiroshima’ image-shift to a Peace Memorial City - Alkazei, Allam; Matsubara, Kosuke (International Planning History Society Proceedings, 2018)
In the wake of war, cities’ path to recovery is hindered by a large-scale destruction which is usually combined with issues such as post-war financial difficulties, and complex property rights. During reconstruction, urban areas encounter different drivers of recovery that define the future direction of